A woman with a chain of nodules lesion - Jamani, Nurjasmine Aida; Jahn Kassim, Puteri Shanaz; Che Yusof, Mohd Daud (Oman Medical Specialty Board, 2017)
Case history A 50-year-old woman with underlying Type 2 diabetes mellitus presented with multiple non-tender nodules over the ventral aspect of her forearm for 3 months duration following scratches by a domestic cat, which had been euthanized for an undiagnosed cutaneous disease. She is otherwise well with no other constitutional symptoms. Examination revealed multiple well with no other constitutional symptoms. Examination revealed multiple well demarcated non-fluctuant nodular lesions in her left wrist extending to the forearm with varying sizes. Some of the lesions appeared to be erythematous while others were hyperpigmented. Other physical examinations were unremarkable.